Process and food engineering studies - Mohd. Nordin, Ibrahim, Assoc. Prof. Dr.; Yus Aniza, Yusof, Assoc. Prof. Dr.; Rosnita, A. Talib, Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.my/